Views of educators about organic school which is an alternative model in education - Turan, Mehmet; Caliskan, Emir Feridun (International Journal of Research in Education and Science, 2018)
The purpose of this research is to identify the general opinions of the educators on the Organic School Model (education inspectors, academicians, school administrators, primary and preschool teachers). The research was designed within the framework of qualitative research approach and phenomenology method, which is one of the qualitative research designs. As the means of data collection semi-structured interview technique was used. Before stating their opinions about school model, participants were watched a package. The necessary information and visuals about school are available in that video. Especially there was given information about that school model focusing on the four components of education program; objectives, content, education process and evaluation. And then four questions in the interview form were asked to the participants. As a result of the research, an alternative school model peculiar to Turkey was developed and that model was approved by the educators. It is thought that this school will prepare students for real life, involve them in nature, provide them with learning through experience and improve their affective and psychomotor skills besides cognitive ones. In short, this school model was considered to be an important study contributing to education if could be adopted. © 2018, International Journal of Research in Education and Science. All rights reserved.
Keywords: Alternative school; Organic education; Organic school